2020
DOI: 10.1002/pits.22367
|View full text |Cite
|
Sign up to set email alerts
|

School psychologists and suicide risk assessment: Role perception and competency

Abstract: As the second leading cause of death for adolescents, suicide is a major concern for school personnel. School psychologists' training in mental health makes them wellpositioned to lead in suicide prevention efforts; however, studies have shown a lack of preparedness in crisis intervention and, more specifically, suicide risk assessment.This study surveyed practicing school psychologists (N = 92) to explore their perception of both their role and competency in suicide risk assessment. Suicide risk assessment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…No que diz respeito à categoria 1 (35% dos estudos), percepção de papéis e/ou competências de avaliação psicológica de profissionais de psicologia escolar e afins, os estudos evidenciaram uma grande variabilidade de práticas de avaliação psicológica escolar, entre as quais estudo de competências e papéis de psicólogos escolares na avaliação para o risco de suicídio (Erps et al, 2020), verificação de dados de raça e influência na tomada de decisões de psicólogos escolares (Sullivan et al, 2019), utilização do instrumento WISC-V no esclarecimento diagnóstico de casos de crianças com dupla excepcionalidade (superdotadas e com dificuldade de aprendizado) (Silverman & Gilman, 2020), e análise de erros mais comuns no uso da WISC-IV e de seus subtestes mais problemáticos (Oak et al, 2018) (Quadro 2). De entre as práticas referentes à categoria 1, destacaram-se, ainda, a identificação, via inquéritos (surveys), de perfis de utilizadores e de utilização de instrumentos por psicólogos (Benson et al, 2019a;Benson et al, 2019b;Cochrane et al, 2019;Johnson et al, 2019;Preast & Burns, 2019;Seabra-Santos et al, 2019, Maki, Burns & Sullivan, 2018Aiello et al, 2017 2017) (Quadro 2), a discussão de medidas de prevenção, avaliação de risco e estratégias de intervenção de psicólogos e conselheiros escolares ao abordar o cyberbullying (Elbedour et al, 2020) (Quadro 3), os papéis de psicólogos escolares para crianças pequenas (Albritton et al, 2019) (Quadro 3) e o uso de entrevistas telefônicas para identificar as forças, fraquezas e possibilidades de desenvolvimento da "aprendizagem baseada em problemas" (Problem-based Learning) (Dunsmuir et al, 2017) (Quadro 3).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…No que diz respeito à categoria 1 (35% dos estudos), percepção de papéis e/ou competências de avaliação psicológica de profissionais de psicologia escolar e afins, os estudos evidenciaram uma grande variabilidade de práticas de avaliação psicológica escolar, entre as quais estudo de competências e papéis de psicólogos escolares na avaliação para o risco de suicídio (Erps et al, 2020), verificação de dados de raça e influência na tomada de decisões de psicólogos escolares (Sullivan et al, 2019), utilização do instrumento WISC-V no esclarecimento diagnóstico de casos de crianças com dupla excepcionalidade (superdotadas e com dificuldade de aprendizado) (Silverman & Gilman, 2020), e análise de erros mais comuns no uso da WISC-IV e de seus subtestes mais problemáticos (Oak et al, 2018) (Quadro 2). De entre as práticas referentes à categoria 1, destacaram-se, ainda, a identificação, via inquéritos (surveys), de perfis de utilizadores e de utilização de instrumentos por psicólogos (Benson et al, 2019a;Benson et al, 2019b;Cochrane et al, 2019;Johnson et al, 2019;Preast & Burns, 2019;Seabra-Santos et al, 2019, Maki, Burns & Sullivan, 2018Aiello et al, 2017 2017) (Quadro 2), a discussão de medidas de prevenção, avaliação de risco e estratégias de intervenção de psicólogos e conselheiros escolares ao abordar o cyberbullying (Elbedour et al, 2020) (Quadro 3), os papéis de psicólogos escolares para crianças pequenas (Albritton et al, 2019) (Quadro 3) e o uso de entrevistas telefônicas para identificar as forças, fraquezas e possibilidades de desenvolvimento da "aprendizagem baseada em problemas" (Problem-based Learning) (Dunsmuir et al, 2017) (Quadro 3).…”
Section: Resultsunclassified
“…Embora os testes de inteligência padronizados continuem a predominar dentre as práticas de avaliação psicológica escolar, os questionários permanecem como a base de todos os processos de avaliação e obtenção de informações (Erps et al 2020;Ruether et al 2019;Seabra-Santos et al 2019;Aiello et al 2017;Watson et al 2016;Johnson et al 2015;Bourke & Dharan, 2015). Os itens destes questionários podem, eventualmente, vir a ser utilizados como guia de avaliação em contextos específicos.…”
Section: Práticas De Avaliação Psicológica Escolar Estáveis Ao Longo Do Tempounclassified
“…Formulations about suicide-related risk and ongoing treatment provided to individuals with suicide-related thoughts and behaviors (STB) are considered to be among the most stressful aspects of clinical practice, wrought with ethical challenges and taking a heavy toll on clinicians’ emotions (Jobes et al, 2008; Rothes et al, 2014). School psychologists, who are often expected to provide tertiary interventions to students experiencing a suicide-related crisis, are among the professionals facing these challenges (Brown et al, 2018; Erps et al, 2020). In addition to their role in the risk formulation process, school psychologists may also face decisions about how best to support adolescents, as they return to school following hospitalization for a suicide-related crisis (Marraccini et al, 2019).…”
Section: Suicide-related Risk and Recoverymentioning
confidence: 99%
“…Within the context of suicide intervention specifically, similar barriers to collaboration likely apply. Erps et al (2020) found that most school psychologists (87%) reported adequate knowledge of community mental health providers with whom they could collaborate for student referrals regarding suicidal thoughts or behaviors. Other findings, however, suggest that relatively few school psychologists (31%) have access to sufficient community mental health resources, and that many find it difficult to promote adequate follow‐up care when collaborating with external providers (e.g., community mental health providers not returning phone calls; Brown et al, 2018).…”
Section: School Psychologists As Collaborators When Supporting Mental...mentioning
confidence: 99%